(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Investigation on in vivo effects of copper (Cu) on the ultrastructure of P. JavanicusÂ liver was carried out using transmission electron microscopy (TEM). The addition of sublethal concentration of 5 mg/L of Cu caused abnormalities on the bile canaliculi (BC) including dilation and elongation compared to control and at lower concentrations of copper with a normal round shape form. Findings from this study support an alternative histological assessment of the effects of Cu concentration on P. Javanicus liver.